Determination of Dopamine in the Presence of Ascorbic Acid by Nafion and Single-Walled Carbon Nanotube Film Modified on Carbon Fiber Microelectrode - Haesang Jeong; Seungwon Jeon (Sensors, 2008)
Carbon fiber microelectrode (CFME) modified by Nafion and single-walled carbon nanotubes (SWNTs) was studied by voltammetric methods in phosphate buffer saline (PBS) solution at pH 7.4. The Nafion-SWNTs/CFME modified microelectrode exhibited strongly enhanced voltammetric sensitivity and selectivity towards dopamine (DA) determination in the presence of ascorbic acid (AA). Nafion-SWNTs film accelerated the electron transfer reaction of DA, but Nafion film as a negatively charged polymer restrained the electrochemical response of AA. Voltammetric techniques separated the anodic peaks of DA and AA, and the interference from AA was effectively excluded from DA determination. Linear calibration plots were obtained in the DA concentration range of 10 nM - 10 ÃŽÂ¼M and the detection limit of the anodic current was determined to be 5 nM at a signal-to-noise ratio of 3. The study results demonstrate that DA can be determined without any interference from AA at the modified microelectrode, thereby increasing the sensitivity, selectivity, and reproducibility and stability.